THE DETECTIONOF CALCIFICATION IN KIDNEYS OF THE LAYING HENS(GALLUS GALLUSDOMESTICUS) BY USING THE HISTOLOGICAL AND IMMUNOHISTOCHEMICAL TECHNIQUES - Ahmed Al- badri; Ali Bargooth; Esraa Zegyer (Basrah Journal of Veterinary Research)
The present research was planned to realize and determine the calcification inthe kidneys of two ages (18 months and 24 months) of laying hens. There are no cleardifferences in histological appearance by using (H&E) stain between to ages, butthere are higher significant differences in the height of epithelium cells and lowersignificant differences in the lumen of renal tubules in the kidneys of laying hens for(24 months) than in the (18 months). By using special dyes (Van Kossa)revelateddeposits of calcium salts and using immunohistochemistry method, theresults showed presence of calcification in form of small foci in varying sizes bearingwithin them brown to dark color calcium deposits in the glomerulus, the epitheliumlayer and basement membrane of the renal tubules and between them. In general thecalcified foci in different areas of kidneys in the 24 month age increase than in the 18months age.